The Impact Of The Implementation Of Good Corporate Governance (GCG) Components On Islamic Banking Performance (Study on Islamic Commercial Banks in BI) - Saraswati, Leli; Mukhzarudfa, Mukhzarudfa; Setiawan, Dedi (Jurnal Cakrawala Akuntansi, 2023)
This study aims to analyze the influence of good corporate governance components—specifically the board of commissioners, sharia supervisory board, audit committee, and institutional ownership—on the performance of Islamic banks. The research focuses on Islamic commercial banks in Indonesia over the 2014–2018 period. The data were obtained from the annual reports of selected banks using a purposive sampling method. A multiple linear regression approach was employed, supported by classical assumption tests and hypothesis testing through regression analysis. The findings indicate that the combined implementation of good corporate governance components has a significant effect on the performance of Islamic banks. Among the individual variables, the audit committee shows a strong association with improved bank performance, highlighting the importance of oversight functions in supporting operational efficiency and accountability. In contrast, the board of commissioners, sharia supervisory board, and institutional ownership did not individually show a meaningful impact on performance during the observed period. The implications of this study suggest that while governance mechanisms are crucial, their effectiveness may vary depending on the role and function of each component. Strengthening the role of audit committees in Islamic banking could enhance financial discipline and transparency. Furthermore, regulatory bodies and stakeholders may need to reassess the effectiveness of other governance elements to better align them with the unique principles of sharia banking. These insights contribute to a deeper understanding of governance dynamics in Islamic financial institutions and support efforts to improve corporate governance practices in the sector.